Evaluation of the Quilting Technique for Reduction of Postmastectomy Seroma: A Randomized Controlled Study. (12th July 2015) - Khater, Ashraf; Elnahas, Waleed; Roshdy, Sameh; Farouk, Omar; Senbel, Ahmed; Fathi, Adel; Hamed, EmadEldeen; Abdelkhalek, Mohamed; Ghazy, Hosam
Abstract : Background . Postmastectomy seroma causes patients' discomfort, delays starting the adjuvant therapy, and may increase the possibility of surgical site infection. Objective . To evaluate quilting of the mastectomy flaps with obliteration of the axillary space in reducing postmastectomy seroma. Methods . A randomized controlled study was carried out among 120 females who were candidates for mastectomy and axillary clearance. The intervention group (N = 60 ) with quilting and the control group without quilting. All patients were followed up routinely for immediate and late complications. Results . There were no significant differences between the two groups as regards the demographic characteristics, postoperative pathological finding, and the immediate postoperative complications. The incidence of seroma was significantly lower in the intervention group compared with the control group (20% versus 78.3%, P < 0.001 ). Additionally, the intervention group had a shorter duration till seroma resolution (9 days versus 11 days, P < 0.001 ) and a smaller volume of drainage (710 mL versus 1160 mL, P < 0.001 ) compared with the control group. Conclusion . The use of mastectomy with quilting of flaps and obliteration of the axillary space is an efficient method to significantly reduce the postoperative seroma in addition to significantly reducing the duration and volume of wound drainage. Therefore we recommend quilting of flaps as a routine step at the end of any mastectomy.